Spray-dried mucoadhesives for intravesical drug delivery using N-acetylcysteine- and glutathione-glycol chitosan conjugates. (1st October 2016) - Denora, Nunzio; Lopedota, Angela; Perrone, Mara; Laquintana, Valentino; Iacobazzi, Rosa M.; Milella, Antonella; Fanizza, Elisabetta; Depalo, Nicoletta; Cutrignelli, Annalisa; Lopalco, Antonio; Franco, Massimo
Graphical abstract: Abstract: This work describes N -acetylcysteine (NAC)- and glutathione (GSH)-glycol chitosan (GC) polymer conjugates engineered as potential platform useful to formulate micro-(MP) and nano-(NP) particles via spray-drying techniques. These conjugates are mucoadhesive over the range of urine pH, 5.0–7.0, which makes them advantageous for intravesical drug delivery and treatment of local bladder diseases. NAC- and GSH-GC conjugates were generated with a synthetic approach optimizing reaction times and purification in order to minimize the oxidation of thiol groups. In this way, the resulting amount of free thiol groups immobilized per gram of NAC- and GSH-GC conjugates was 6.3 and 3.6 mmol, respectively. These polymers were completely characterized by molecular weight, surface sulfur content, solubility at different pH values, substitution and swelling degree. Mucoadhesion properties were evaluated in artificial urine by turbidimetric and zeta (ζ)-potential measurements demonstrating good mucoadhesion properties, in particular for NAC-GC at pH 5.0. Starting from the thiolated polymers, MP and NP were prepared using both the Büchi B-191 and Nano Büchi B-90 spray dryers, respectively. The resulting two formulations were evaluated for yield, size, oxidation of thiol groups and ex-vivo mucoadhesion. The new spray drying technique provided NP of suitable size (<1 μm) for catheter administration, low degree of oxidation, and sufficient mucoadhesion property with 9% and 18% of GSH- and NAC-GC based NP retained on pig mucosa bladder after 3 h of exposure, respectively. Statement of Significance: The aim of the present study was first to optimize the synthesis of NAC-GC and GSH-GC, and preserve the oxidation state of the thiol moieties by introducing several optimizations of the already reported synthetic procedures that increase the mucoadhesive properties and avoid pH-dependent aggregation. Second, starting from these optimized thiomers, we studied the feasibility of manufacturing MP and NP by spray-drying techniques. The aim of this second step was to produce mucoadhesive drug delivery systems of adequate size for vesical administration by catheter, and comparable mucoadhesive properties with respect to the processed polymers, avoiding thiolic oxidation during the formulation. MP with acceptable size produced by spray-dryer Büchi B-191 were compared with NP made with the apparatus Nano Büchi B-90.